2017
DOI: 10.1007/s00405-017-4475-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of cigarette smoking on the olfactory neuroepithelium of New Zealand white rabbit, using scanning electron microscope

Abstract: To detect ultra-structural changes of Rabbit's olfactory neuro-epithelium using scanning electron microscope after exposure to cigarette smoking. Sixty six rabbits (Pathogen free New Zealand white rabbits weighing 1-1.5 kg included in the study were randomly assigned into one of three groups: control group did not expose to cigarette smoking, study group 1 was exposed to cigarette smoking for 3 months and study group 2 was exposed to cigarette smoking 3 months and then stopped for 2 months. Olfactory neuro-epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
2
8
1
Order By: Relevance
“…Previous studies have shown that increased expressions of pro-inflammatory cytokines, such as interleukin-1β, intercellular adhesion molecule 1, nuclear factor-κB, glucocorticoid receptor-β, transforming growth factor-β1 and mucin 4, in nasal polyp tissues were associated with a poor response to GC treatment, suggesting these pro-inflammatory cytokines might be involved in pathogenesis of GC resistance and could potentially be as biomarkers of GC insensitivity in CRSwNP patients [ 11 , 19 , 20 ]. In terms of clinical parameters, we have reported that smell loss score, ethmoid osteitis index and blood eosinophil number and ratio could be used as the surrogate markers for the diagnosis of eosinophilic CRS [ 21 ]. Recently, Meng et al [ 9 ] found that the ratio of the CT scores for the ethmoid sinus and maxillary sinus (E/M ratio) had superior predictive value over other clinical parameters including blood eosinophil counts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that increased expressions of pro-inflammatory cytokines, such as interleukin-1β, intercellular adhesion molecule 1, nuclear factor-κB, glucocorticoid receptor-β, transforming growth factor-β1 and mucin 4, in nasal polyp tissues were associated with a poor response to GC treatment, suggesting these pro-inflammatory cytokines might be involved in pathogenesis of GC resistance and could potentially be as biomarkers of GC insensitivity in CRSwNP patients [ 11 , 19 , 20 ]. In terms of clinical parameters, we have reported that smell loss score, ethmoid osteitis index and blood eosinophil number and ratio could be used as the surrogate markers for the diagnosis of eosinophilic CRS [ 21 ]. Recently, Meng et al [ 9 ] found that the ratio of the CT scores for the ethmoid sinus and maxillary sinus (E/M ratio) had superior predictive value over other clinical parameters including blood eosinophil counts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that smoking is one of the leading causes of olfactory impairment (44,45). Squamous metaplasia and altered shape of olfactory receptor neurons have been discovered during the histological analyses of smokers' olfactory epithelium (46), which has been confirmed in animal studies (47,48). The olfactory function is about equally affected by passive smoking (49).…”
Section: Olfactory Dysfunctionmentioning
confidence: 89%
“… 18 In smoke‐exposed rabbits, Iskander et al found a loss of sustentacular cell microvilli, a reduction in the distribution of specialized cilia on olfactory receptor cells, and respiratory metaplasia. 19 …”
Section: Discussionmentioning
confidence: 99%
“…18 In smoke-exposed rabbits, Iskander et al found a loss of sustentacular cell microvilli, a reduction in the distribution of specialized cilia on olfactory receptor cells, and respiratory metaplasia. 19 Passive smoking can be just as hazardous in many ways as active smoking. The effect of passive smoking on the nasal mucosa and nasal mucociliary clearance has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%